2021
DOI: 10.48550/arxiv.2106.12933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GNMR: A provable one-line algorithm for low rank matrix recovery

Abstract: Low rank matrix recovery problems, including matrix completion and matrix sensing, appear in a broad range of applications. In this work we present GNMR -an extremely simple iterative algorithm for low rank matrix recovery, based on a Gauss-Newton linearization. On the theoretical front, we derive recovery guarantees for GNMR in both the matrix sensing and matrix completion settings. A key property of GNMR is that it implicitly keeps the factor matrices approximately balanced throughout its iterations. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…By combining assumption (7) and Theorem 3.3, the sensing operator A satisfies a min{d 1 , d 2 }-RIP with a constant δ ≤ 1/2. Hence, as in the proof of Lemma 4.2 in [ZN22], the minimal nonzero singular value of…”
Section: D2 Proof Of Proposition 52mentioning
confidence: 72%
See 3 more Smart Citations
“…By combining assumption (7) and Theorem 3.3, the sensing operator A satisfies a min{d 1 , d 2 }-RIP with a constant δ ≤ 1/2. Hence, as in the proof of Lemma 4.2 in [ZN22], the minimal nonzero singular value of…”
Section: D2 Proof Of Proposition 52mentioning
confidence: 72%
“…Let K = ker L (Ut,Vt) . By combining our RIP guarantee (Theorem 3.3) with the second part of Lemma 4.4 in [ZN22] which holds due to our Lemma D.1,…”
Section: D1 a Computationally Efficient Way To Find The Minimal Norm ...mentioning
confidence: 96%
See 2 more Smart Citations
“…It is still a challenge to recover missing gene expression values more effectively in scRNA-seq data. Previous studies ( Narayanamurthy et al, 2019 ; Nguyen et al, 2019 ; Kummerle and Verdun, 2021 ; Zilber and Nadler, 2021 ) have shown that the low-rank matrix can recover missing values based on a few observable entries due to its low-rank structure. Considering this, we apply low-rank matrix completion to missing value imputation in scRNA-seq data.…”
Section: Introductionmentioning
confidence: 99%